Association of IL23R p.381Gln and ATG16L1 p.197Ala with Crohn disease in the Czech population - Dusatkova, Petra; Hradsky, Ondrej; Lenicek, Martin; Bronsky, Jiri; Nevoral, Jiri; Kotalova, Radana; Bajerova, Katerina; Vitek, Libor; Lukas, Milan; Cinek, Ondrej (Journal of pediatric gastroenterology and nutrition, 2009)
An association of variants in the genes encoding the interleukin 23 receptor (IL23R, p.Arg381Gln, rs11209026), and the autophagy-related gene 16-like 1 (ATG16L1, p.Ala197Thr, rs2241880) with Crohn disease (CD) was identified by whole genome association studies, and subsequently confirmed by other works. The aim of this study was to assess this association in the Czech population. In a case-control study 333 patients with CD (137 paediatric and 196 adult-onset) and 499 unrelated healthy controls were genotyped using TaqMan SNP assays. The IL23R p.381Gln allele was protective against CD in the Czech population (allelic frequency 3.2% in patients vs 5.5% in control subjects; OR 0.56, 95% CI 0.33-0.93, P=0.02). ATG16L1 p.197Ala allele conferred increased risk of CD (allelic frequency 60% in patients vs 51% in controls; OR 1.25, 95% CI 1.02-1.52, P=0.03). There was no appreciable difference in the effect of the associated alleles across the strata of CARD15-conferred risk. The IL23R and ATG16L1 variants did not influence the age at diagnosis, and in the genotype-phenotype analysis, the only detected association was a weak one between IL23R p.381Gln and involvement of the upper gastrointestinal tract (uncorrected P=0.031). We confirmed the role of IL23R and ATG16L1 in the CD susceptibility in the Czech population, and found a weak protective effect of IL23R p.381Gln against upper gastrointestinal tract involvement.